Multiple sclerosis—a quiet revolution - Ransohoff, Richard M. (Nat Rev Neurol, 2015)
Multiple sclerosis (MS) has been thought to be a complex and indecipherable disease, and poorly understood with regards to aetiology. Here, we suggest an emphatically positive view of progress over several decades in the understanding and treatment of MS, particularly focusing on advances made within the past 20 years. As with virtually all complex disorders, MS is caused by the interaction of genetic and environmental factors. In recent years, formidable biochemical, bioinformatic, epidemiological and neuroimaging tools have been brought to bear on research into the causes of MS. While susceptibility to the disease is now relatively well accounted for, disease course is not and remains a salient challenge. In the therapeutic realm, numerous agents have become available, reflecting the fact that the disease can be attacked successfully at many levels and using varied strategies. Tailoring therapies to individuals, risk mitigation and selection of first-line as compared with second-line medications remain to be completed. In our view, the MS landscape has been comprehensively and irreversibly transformed by this progress. Here we focus on MS therapeutics—the most meaningful outcome of research efforts.